HSF-1 attenuates isoflurane-induced cognitive dysfunction by inhibiting TLR2 expression - Jia, Xu; Huang, Xuezhu; Duan, Mingda; Qiu, Wei; Zhang, Xuanbo; Wang, Xin (Tropical journal of pharmaceutical research, 2022)
Purpose: To investigate the regulatory effects of heat shock factor 1 (HSF-1) in the progression of postoperative cognitive dysfunction (POCD). Methods: Isoflurane (ISO)-induced POCD model in rats was established to determine the role of HSF-1 in POCD. Morris water maze test was used to evaluate the learning and memory abilities of the POCD rats while mRNA and protein levels of HSF-1 were determined by RNA extraction/quantitative real-time polymerase chain reaction (RT-qPCR) and western blot analysis, respectively. Results: The mRNA and protein levels of HSF-1 were significantly reduced in ISO model, but OE-HSF-1 treatment significantly elevated HSF-1 level (p < 0.05). ISO treatment also significantly decreased escape latency but increased the decreased target quadrant of the rats, while HSF-1 upregulation reversed these effects (p < 0.05). Additionally, HSF-1 alleviated ISO-induced hippocampal injury, improved ISO-induced hippocampal inflammation, and inhibited ISO-induced hippocampal apoptosis. Furthermore, HSF-1 was modulated by POCD via TLR2/NF-κB pathway (p < 0.05). Conclusion: HSF-1 attenuates ISO-induced cognitive dysfunction by suppressing TLR2 expression. This activity provides a potential strategy to prevent POCD via HSF-1.